ORGANIC FOOD AND TRADITIONAL WAY OF FARMING AS THE DEVELOPMENT POSSIBILITY OF SERBIA - Boškov, Veronika (International Journal of Economic Practice and Policy, 2015)
Production of organic food brings the possibility of development of rural areas where pollution is minimal, so that food produced in such conditions is better because of the lower levels of chemicals spent in the production process and thus has a positive effect on human health. The return to the traditional way of production brings secure economic benefit to producers. Production of organic food opens up the possibility of economic development and the expansion of exports.
Keywords: Organic food; human health; economic development